Syaykh Muhammad Salim Muhaysin: Tokoh Ilmu Qira’at di Abad ke 20 - Mohamad, Sabri; Hj. Mohd. Yusoff, Zulkifli (Jurnal Usuluddin, 2010)
This article discusses about Syaykh Muhammad Salim Muhaysin as one of the intellectuals of science of Qira’at in the 20th century. The focal objective of this research is to introduce him as one of the enormous scholars of science of Qira’at that had an involvement especially in the science of Qira’at Quraniyyah. The exposure of this scholar is significant due to the fact that none of the writing has comprehensively introduced him to the public. It is a textual analysis and field work study based research. This study concludes that Syaykh Muhaysin is one of the productive and outstanding scholars of science of Qira’at that had a great contribution to this area of specialization and others via the route of teaching, writing and spreading the knowledge.